2018
DOI: 10.1111/wrr.12613
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of pressure ulcers after defect reconstruction

Abstract: Patients suffering from pressure ulcers remain to be a challenging task for nursing staff and doctors in the daily clinical management, putting-notably in the case of recurrences-additional strain on the constantly reduced resources in public healthcare. We aimed to assess the risk factors for the recurrence of pressure ulcers at our institution, a tertiary referral center. In this retrospective analysis of patients admitted to our division we identified risk factors for pressure ulcer recurrence. The hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
4
22
2
2
Order By: Relevance
“…ALB has commonly been used as a nutritional assessment indicator. It was reported that ALB was a simple biomarker of wound healing in patients suffering from ulcers [34][35][36]. As consistent with previous researches, our study also indicated that a higher level of ALB was facilitated to ulcer healing.…”
Section: Discussionsupporting
confidence: 92%
“…ALB has commonly been used as a nutritional assessment indicator. It was reported that ALB was a simple biomarker of wound healing in patients suffering from ulcers [34][35][36]. As consistent with previous researches, our study also indicated that a higher level of ALB was facilitated to ulcer healing.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the wounds in this study were over the ischial tuberosities, which is consistent with previously published literature . This relates to the fact that most paralysed patients spend much of their day sitting in their manual or power wheelchairs, and the seating systems are unfortunately not always optimised.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the wounds in this study were over the ischial tuberosities, which is consistent with previously published literature. 4,[7][8][9][10] This relates to the fact that most paralysed patients spend much of their day sitting in their manual or power wheelchairs, and the seating systems are unfortunately not always optimised. Often, relating to their SCI and muscle wasting, there also is a lack of good-quality soft tissue coverage over the bony prominences in this area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations